El discurso colonialista en la internacionalización y sostenibilidad: una mirada desde América Latina - Gomez-Trujillo, Ana Maria (2021)
This article seeks to show the internationalization process and the implementation of sustainability practices as manifestations of colonialism in the Latin American context which are not adjusted to their local realities. The need to address these concepts from a local perspective that takes into account the uniqueness of the organization's problems from the Latin American reality is highlighted. Thus, internationalization can be conceived in a way that promotes sustainable regional development of the so-called southern countries and reduces the dependency relationship with the northern hegemony, for which it is necessary to create theories that take into account the particularities of the periphery companies and highlight their differences with those belonging to the great and traditional world powers